Peran Konsep Diri, Dukungan Orang Tua dan Penyesuaian Sosial Terhadap Optimisme Siswa SMK Negeri 2 Klaten - Susatyo, Widoyoko Pratondo, Dr. Sri Lestari, M.Si s (2016)
One of the difficulties experienced in the learning process and can impede studentS achievement progress is optisme problem, because it causes students are not confident, not confident in their ability and being hesitant in taking decisions. This study aimed; (1) The relationship between self-concept, parental support, and social adjustment with optimism in students; (2) Contribution of parental support and social adjustment towards optimism in students; (3) The level of self-concept, parental support, social adjustment and optimism in students. The subject of the research is the students of class X, XI and XII SMK N 2 Klaten as 197 students. Collecting data using a scale between self-concept, parental support and social adjustment with optimism. Data were analyzed using regression of three predictors. Conclusion of the study stated that there was a significant relationship between self-concept, parental support and social adjustment with optimism. Based on the results of analysis on the self-concept on the subject of research is high, the parental support classified as moderate; social adjustment research on the subject is high and optimism on the subject of research is moderate.